2016
DOI: 10.1128/mbio.01054-16
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous Diffusible Signal Factor Production and Responsiveness of the Xylella fastidiosa Rpf System

Abstract: Cell density-dependent regulation of gene expression in Xylella fastidiosa that is crucial to its switching between plant hosts and insect vectors is dependent on RpfF and its production of 2-enoic acids known as diffusible signal factor (DSF). We show that X. fastidiosa produces a particularly large variety of similar, relatively long-chain-length 2-enoic acids that are active in modulating gene expression. Both X. fastidiosa itself and a Pantoea agglomerans surrogate host harboring X. fastidiosa RpfF (XfRpfF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 40 publications
0
53
0
3
Order By: Relevance
“…A reversed‐phase HPLC analysis (adapted from Ionescu et al) was performed on an Ettan LC system (GE Healthcare Life Sciences) equipped with an Acclaim PepMap100 C18 column (3 μm, 250 mm × 75 μm; Thermo Scientific) with as solvent A 0.1% TFA in H 2 O (Milli‐Q; MQ) and solvent B 0.1% TFA in methanol. A 15‐min gradient starting from 25% solvent B and increasing to 100% solvent B was applied for the separation.…”
Section: Methodsmentioning
confidence: 99%
“…A reversed‐phase HPLC analysis (adapted from Ionescu et al) was performed on an Ettan LC system (GE Healthcare Life Sciences) equipped with an Acclaim PepMap100 C18 column (3 μm, 250 mm × 75 μm; Thermo Scientific) with as solvent A 0.1% TFA in H 2 O (Milli‐Q; MQ) and solvent B 0.1% TFA in methanol. A 15‐min gradient starting from 25% solvent B and increasing to 100% solvent B was applied for the separation.…”
Section: Methodsmentioning
confidence: 99%
“…The studies conducted by Ionescu et al (38) showed that in X. fastidiosa cis-2-tetradecenic acid (C 14 :Δ 2 , XfDSF) and cis-2-hexadecenic acid (C 16 :Δ 2 , XfDSF2) are the strongest gene expression activators. X. fastidiosa and X. campestris were used to show the structural and isomeric effect of DSF molecules on the activation of DSF-dependent processes (the production of extracellular enzymes).…”
Section: Communication Of Microorganisms Via Diffusible Signal Factorsmentioning
confidence: 99%
“…Saturated fatty acids, competing for the RpfC receptors, reduce the activation of processes conditioned by rpf genes, i.e. autoaggregative behavior and biofilm formation (35,38,39,45,46). Reduction of DSFs activity and an increase in AI-2 concentration results in the transformation of some coccoid H. pylori forms to the spiral morphotype, followed by chemorepulsion from the AI-2 source and migration in search of new niches in the gastric environment (6,17,(30)(31)(32)44).…”
Section: The Holistic Model Of H Pylori Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-to-cell signaling mediated by a fatty acid diffusible signaling factor (DSF) may also show different chemical structure according to strain [27][28][29]. Regulation of pathogenicity factors (rpf) cluster [27,[30][31][32] as well as DSF and cyclic di-guanosine monophosphate [33,34] were also critical for biofilm formation, plant virulence, and insect transmission. The complete genome of the CoDiRO strain is not currently available, while assessment of the genome diversity of CoDiRO isolates has been carried out [35][36][37].…”
Section: Pathogen/host Interactionmentioning
confidence: 99%